UJI EFEK ANTIMITOSIS EKSTRAK ETANOL DAUN WUNGU (Graptophyllum pictum (L.) Griff.) DENGAN METODE PENGHAMBATAN PEMBELAHAN SEL TELUR (Tripneustes gratilla L.) TERFERTILISASI - Sitti Amirah (Fakultas Farmasi UMI, 2015)
Antimitotic assay is one of the toxicity assay methods widely used in detection of cytotoxic activity of new compounds from natural materials. This research aimed to examine the effects of antimitotic and determine the IC50 and IC80 values of the ethanol extract of purple leaves with method of fertilized egg cell division inhibition Tripneustes gratilla L. The cell observation were visually carried out under a microscope by counting the number of cells that divided and did not divide after being incubated for ± 2 hours. The results of this research showed that the IC50 and IC80 value of ethanol extract of purple leaves are 2,275 x 10-2 µg/ml and 1,54x10-2 mg / ml respectively. Based on the values, the ethanol extract of purple leaves is active as an antimitotic, despite the potential values can be lower than vincristine which can inhibit 80% egg cell Tripneustes gratilla L. fertilized with IC50 and IC80 values of 1,462 x 10-4 µg/ml and 4.69x10-5 mg/ml.